2001
DOI: 10.1016/s0014-5793(01)02497-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical unfolding of single filamin A (ABP‐280) molecules detected by atomic force microscopy

Abstract: Filamin A (ABP-280), which is an actin-binding protein of 560 kDa as a dimer, can, together with actin filaments, produce an isotropic cross-linked three-dimensional network (actin/filamin A gel) that plays an important role in mechanical responses of cells in processes such as maintenance of membrane stability and translational locomotion. In this study, we investigated the mechanical properties of single filamin A molecules using atomic force microscopy. In force^extension curves, we observed sawtooth patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
112
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 24 publications
(33 reference statements)
13
112
1
Order By: Relevance
“…The mechanical response of the composite FLNa-F-actin networks eludes either the current theoretical models for entangled F-actin solutions or those for rigidly cross-linked F-actin networks. Instead, we speculate that the FLNa cross-links mediate the dynamic nonlinear mechanical response of these networks through an interplay between the nonlinear divergence of the stiffness of individual semiflexible FLNa cross-links with a force-and time-dependent unfolding of sheets within the FLNa molecule [15] as well as binding kinetics of the FLNa molecule with F-actin. Alternatively, current models of prestressed structures suggest that their mechanical response depends very weakly on the elasticity of the individual elements [23].…”
Section: Prl 96 088102 (2006) P H Y S I C a L R E V I E W L E T T E mentioning
confidence: 95%
See 2 more Smart Citations
“…The mechanical response of the composite FLNa-F-actin networks eludes either the current theoretical models for entangled F-actin solutions or those for rigidly cross-linked F-actin networks. Instead, we speculate that the FLNa cross-links mediate the dynamic nonlinear mechanical response of these networks through an interplay between the nonlinear divergence of the stiffness of individual semiflexible FLNa cross-links with a force-and time-dependent unfolding of sheets within the FLNa molecule [15] as well as binding kinetics of the FLNa molecule with F-actin. Alternatively, current models of prestressed structures suggest that their mechanical response depends very weakly on the elasticity of the individual elements [23].…”
Section: Prl 96 088102 (2006) P H Y S I C a L R E V I E W L E T T E mentioning
confidence: 95%
“…It is a homodimer consisting of an actin-binding domain, 24 -sheet repeats, and two unstructured sequences of 32 amino acids [14]. Atomic force measurements show that, at small forces, FLNa can be modeled as a wormlike chain with a persistence length of 20 nm [15]. At higher forces of 50 -100 pN, the -sheet repeat sequences reversibly unfold, doubling the contour length [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The compliance of this network is dominated by the flexible cross-linkers, while the much stiffer filaments act mainly as a scaffold for the cross-linkers, ensuring rigidity of the network as a whole. Recent experiments have demonstrated that flexible biological cross-linkers such as filamin can be described as a semiflexible polymer using the wormlike chain (WLC) model [17,18]. The cross-linkers are characterized by their contour length ℓ 0 and persistence length ℓ p [15].…”
mentioning
confidence: 99%
“…Using atomic force microscopy 50 -220 pN have been reported; this unfolding is reversible, and the unfolded chains fold back when the external force is removed (31)(32)(33). The unfolding of the ddFLN rod was particularly interesting as one of the repeats, repeat 4, unfolded in two steps and refolded along the same pathway (33,34).…”
mentioning
confidence: 99%